Transcutaneous Spinal Cord Stimulation Attenuates Blood Pressure Drops in Orthostasis - Natalia N. Beliaeva; Tatiana R. Moshonkina; Oleg V. Mamontov; Elena N. Zharova; Heber Ivan Condori Leandro; Nigar Z. Gasimova; Evgeny N. Mikhaylov (Life, 2022)
Orthostatic hypotension is a complex medical problem with various underlying pathogenic mechanisms and limited modalities for its correction. Since transcutaneous spinal cord stimulation (t-SCS) leads to immediate blood pressure (BP) elevation in a supine position, we suggested that t-SCS may attenuate blood pressure drops in orthostasis. We aimed to evaluate the hemodynamic effects of t-SCS during tilt testing in a feasibility study in three patients with documented orthostatic hypotension. Four sessions on two different days of tilt testing on and off t-SCS were performed on each patient. While tilting with t-SCS off showed typical significant BP drops in every patient, active t-SCS resulted in systemic vascular resistance (SVR) elevation in all patients and significantly higher values of systolic and diastolic BP in two patients. T-SCS requires further investigation on a larger patient population. However, our preliminary results demonstrate its ability for SVR and BP elevation in subjects with severe orthostatic hypotension.